PEMBERDAYAAN KADER IPPNU DALAM UPAYA DETEKSI DINI DAN PENCEGAHAN PENYAKIT TIDAK MENULAR - Yayuk Eliyana; Layla Imroatu Zulaikha; Maimon Sumo (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The increasing risk factors for Non-Communicable Diseases (NCDs) among adolescents require innovative preventive approaches. This community service program aimed to empower cadres of the Nahdlatul Ulama Female Student Association (PAC IPPNU) in Pademawu District as agents for the early detection of NCDs, addressing the challenges of the cadres' low knowledge and practical skills. The method used was the IPOAI (Identifying, Planning, Organizing, Acting, Impact) empowerment model. The program was implemented through hybrid training that integrated interactive lectures and hands-on practice in measuring blood pressure, blood sugar, and Body Mass Index (BMI) for 23 cadres. The program's effectiveness was measured by comparing pre-test and post-test scores for knowledge and an observation checklist for skills. The results showed a significant increase in the cadres' knowledge. The proportion of cadres with "Good" knowledge surged from 13% to 82.6%. In terms of skills, all cadres (100%) became proficient in measuring blood pressure and calculating BMI, while 82.6% of cadres became proficient in checking blood glucose. The analysis indicates that the experiential learning approach with immediate feedback was effective in building competency, although psychological factors posed a challenge for the invasive procedure. This empowerment program proved effective in enhancing the capacity of adolescent cadres. Equipped with health tools handed over for sustainable use, the cadres are expected to become the frontline for NCD promotion and prevention, bridging the healthcare service gap in their community.